Epidemiology of emerging diseases and disorders in cage cultured Pangasius spp. in Pahang, Malaysia - Mansor, Nur Nazifah; Khan Chowdhury, Ahmed Jalal; Ridzuan, Mohd Syafiq; Mohd Khalid, Hazreen Nita; Mahmood, Syakeera (2020)
Pangasius hypophthalmus or famously known by local Malaysians as Patin Hitam is one of the most important sources of food in Malaysia. It is widely cultured in the Peninsular Malaysia especially in Pahang as Patin is a popularly consumed freshwater fish. Global economic interest in the fish has increased its demand in the USA and Europe. However, high mortality due to bacterial and viral infections is the main problem that needs to be solved. Therefore, bacteria in P. hypophthalmus in Pahang is being focused with the factors connected to the prevalence of bacteria and virus in P. hypophthalmus. This research was conducted for two cycles (February–September 2016 and January–August 2017) in different farms in Temerloh and Pekan, Pahang. Bacteria and virus samples were taken from three organs of Patin Hitam which are kidney, liver and spleen. Physical parameters for water quality was measured using a multi-parameter probe sensor (YSI, USA) and chemical parameters were analyzed with DR900 colorimeter (Hach, USA). Bacteria samples were identified using biochemical test kits, API 20NE and 20E, followed by confirmation of the bacteria using Polymerase Chain Reaction (PCR). Virus samples were identified using conventional PCR. There were several bacteria isolated throughout the culture period. The highest prevalence of bacteria found was Aeromonas hydrophila (63%0 followed by Photobacterium damselae (23%), Plesiomonas shigelloids (7%), Pseudomonas luteola (4%) and Pseudomonas fluorescens (3%). There was no virus isolated from these two sites in Pahang River. The susceptible size of Pangasius spp. that was infested by A. hydrophila was 300-400g. Furthermore, risk factors affected the presence of bacteria were different at all sites. However, only ammonia was presence throughout the sampling period at all sites. Sulfide, nitrite, iron and ammonia were were the most significant parameters that have strong associations with the presence of A. hydrophila. Significantly, these results could contribute to better treatment of fish disease and development of standard operating procedure of future fish culture for early disease prevention.